MUDAHNYA DISPENSASI NIKAH TERHADAP MARAKNYA PERKAWINAN DI BAWAH UMUR YANG TERJADI DI DAERAH LAMONGAN - Izzati Choirina; Mifta aliza (JOURNAL SAINS STUDENT RESEARCH, 2023)
The aim of this research is to uncover the reasons behind the rise of hundreds of early marriages in the Lamongan area. Literature studies are used to support this research data. The increase in early marriage in Lamongan Regency is caused by various factors, ranging from social to economic to religious. Due to these factors, the rate of early marriage continues to increase from year to year in Lamongan Regency. Before the Marriage Law was amended, the legal age for marriage was 16 years for women and 19 years for men. This minimum age for women is contrary to the general definition of a child, namely anyone under 18 years of age. After the enactment of Law Number 16 of 2019, the minimum age for women and men was set at 19 years. However, there are still exceptions, called marriage exceptions. The marriage dispensation letter is an exception to the age limit and can be submitted to local authorities by completing a form and several administrative documents. Some time ago, the Lamongan Religious Court (PA) provided data on applications for marriage dispensation letters, most of whom were students, from January to November 2023. In total, there were approximately 301 memos containing various reasons for getting married. A total of 295 applications have been approved, while the remaining six are still being processed. Data shows that 256 teenagers who applied for a marriage license did so to avoid infidelity and adultery, and most children who married early felt they had no other choice.